THE USE OF SLANG IN ONLINE COMMUNICATION: A LINGUISTIC ANALYSIS OF SOCIAL MEDIA DISCOURSE - FITRI, ARYA (Jurnal Smart, 2025)
This study explores the use and understanding of slang in online communication among different age groups, focusing on Generation Z, Millennials, and Generation X+. Using a mixed-method approach, it combines qualitative content analysis of social media (Twitter, TikTok, Reddit) with a quantitative survey on slang familiarity, usage frequency, and social functions. Results show that Generation Z has a much higher understanding and usage of slang, while older generations are less familiar. Slang serves as a tool for expressing identity, humor, and social bonding, though generational gaps may challenge intergenerational communication, emphasizing the need for adaptive strategies and education.